Materi ajar cerpen di SMA dengan Tema Lingkungan berdasarkan Kurikulum 2013 - Juanda Juanda; Azis Azis (Seminar Nasional LP2M UNM, 2019)
Literature, especially short stories as one of the material in Indonesian language subjects is very strategic as a media for implementing environmental awareness character education. The purpose of this study was to explore Kompas short stories with environmental themes to be used as teaching material in high school. The method used in this study is a qualitative descriptive method. The data source used in this study is the Kompas short stories of the 2018 weekly edition of 42 short stories. While the data collected is the result of a review in the compass short stories. Data collection techniques use non-interactive techniques by conducting intensive readings on short stories and actively recording with the content analysis method. This study uses an ecocritical approach. Data validity to test the validity of this study using data triangulation and triangulation methods. Data analysis techniques used an interactive analysis model. Data analysis was carried out by following the models of Miles and Huberman (1992), namely: (1) identifying short stories as research objects, (2) reducing data, (3) presenting data, (4) interpreting data obtained according to theory, and (5) compiling conclusions. This type of research is descriptive qualitative with the content analysis method. Data is collected by inventorying environmental phenomena. The results showed that only 6 short stories were environmental themes, around 14.2%. The Kompas short story entitled Flood of Submissions, Pilgrimage of Love, Father's Durian, Slerok, Second Death, and Men Who Suffer if Praised can be used as teaching material in high school.